2020
DOI: 10.1177/2167702620902130
|View full text |Cite
|
Sign up to set email alerts
|

What Drives Symptom Reduction in Attention Bias Modification Treatment? A Randomized Controlled Experiment in Clinically Anxious Youths

Abstract: Attention-bias modification (ABM) is a novel treatment for anxiety disorders. We tested the contribution of two possible factors implicated in ABM’s efficacy: training of threat-related selective spatial attention and exposure to threat. We also measured general attention control to examine its potential role in treatment effects. A four-arm randomized controlled design was used, which dissociated spatial attention and threat exposure while equating treatment expectancies. One hundred clinically anxious youths… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 53 publications
3
2
0
Order By: Relevance
“…The current results are also consistent with those of other mechanized attention training studies reporting that both active and control conditions had similar and significant treatment effects (e.g. Enock, Hofmann, & McNally, 2014; Linetzky, Pettit, Silverman, Pine, & Bar-Haim, 2020; McNally, Enock, Tsai, & Tousian, 2013; Pergamin-Hight et al . 2016).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The current results are also consistent with those of other mechanized attention training studies reporting that both active and control conditions had similar and significant treatment effects (e.g. Enock, Hofmann, & McNally, 2014; Linetzky, Pettit, Silverman, Pine, & Bar-Haim, 2020; McNally, Enock, Tsai, & Tousian, 2013; Pergamin-Hight et al . 2016).…”
Section: Discussionsupporting
confidence: 91%
“…Basanovic, Notebaert, Grafton, Hirsch, & Clarke, 2017; Chen, Clarke, Watson, MacLeod, & Guastella, 2015; Lazarov et al, 2019; Linetzky et al, 2015; Mogg, Waters, & Bradley, 2017; Pergamin-Hight et al, 2016). Such an explanation is in line with prior studies suggesting that improved executive attention abilities may produce clinical benefits (Bomyea & Amir, 2011; Heeren et al, 2015a; Linetzky et al, 2020). For instance, a recent study in clinically anxious youth showed that improvement in attention control was noted following neutral as well as emotional attention training and that this improvement was associated with symptoms improvement (Linetzky et al, 2020).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our study could not distinguish between these processes, and other paradigms should be used to explore the impact of emotional recognition training on emotional attention in more detail. Third, studies have shown that cognitive bias modification for attention (CBM-A) is also an effective intervention for defects in emotional cognition 24 , 59 , 60 and even can decrease socioemotional problems. 61–63 Further studies are needed to explore the effect of CBM-A on defects in emotional cognition and aggression in juvenile delinquents.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the present study did not include attention control measurement or indices of other cognitive mechanisms that may underlie the efficacy of both ACT and ABM. Future studies are encouraged to incorporate such potential common factors for ACT and ABM (Linetzky, Pettit, Silverman, Pine, & Bar-Haim, 2020 ). The fact that ABV reduced in the two conditions hints that both strengthened attentional control in the context of attentional competition between threat and neutral stimuli (Bardeen, Tull, Daniel, Evenden, & Stevens, 2016 ; Clarke et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%